DO PRIVATE BANKS AFFECT ETHIOPIA'S ECONOMIC GROWTH? - Gadisa, Gemechu; Tigre, Getu (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: Major activities of private sector banks promote changes in a country's economic progress. Many studies have concentrated on the general policy of customer service. As a result, the goal of the study is to look into the impact of private banks on Ethiopia's Gross Domestic Product (GDP) growth. Methods: Time-series data of the National Bank from 2011 to 2020 is studied using a dynamic-factor model that is flexible for multi-variable autoregressive data. Results: The result indicates that mobilization of deposits and domestic investment have a strong positive impact on Gross Domestic Product (GDP), whereas foreign exchange and credit services have a significant negative impact. Conclusion and suggestion: Private banks play an important role in Ethiopia's GDP growth. Therefore, in order to boost economic growth, banks should collect deposits from all over Ethiopia and use them to fund viable investment initiatives.